Rancang Bangun Sistem Informasi E-Kost Sebagai Layanan Penyewaan Serta Pembayaran Berbasis Website Pada Kost Violet - yasinta bertin; Maria Adelvin Londa; Melky Radja (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
The development of technology is getting faster so that it forces people to use information technology as much as possible in all their activities, one of which is for students who will undergo college in a place far from where they live. For this reason, students must find temporary housing until their studies are completed. Due to the large number of residents renting boarding houses, in this case the boarding house owners are still processing payments, recording the name of the boarding house occupants in the book so that they are easily lost and damaged. Therefore, to make it easier for boarding house owners to process boarding payments, a rental information system and boarding payments are made and can also manage payment data properly and computerized. In the process of developing the E-Kost Website, PHP and MySQL programming languages ​​are used, Rapid Application Development (RAD) development techniques. The data flow method used is a structured method consisting of Data Flow Diagrams (DFD) and the testing technique is using Blackbox testing. The purpose of making an E-boarding information system is to make it easier for boarding house owners in the process of rental services and payments Keywords— Violet Kost, E-Kost Rental and Payment Services, PHP, Mysql, Blackbox testing